Pollutant Concentration and Trajectory Patterns of PM2.5 including Meteo Factors in Jakarta City - Dessy Gusnita; Nani Cholianawati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
PM2.5 particulate monitoring has been carried out in South Jakarta. The research objective is to examine the effect of meteorology and pollutant trajectories on PM2.5 conditions based on daily and seasonal patterns from January 2016 to December 2017. The sources of PM2.5 data come from DKI Jakarta BPLHD. The data analysis method uses excel to obtain daily and seasonal PM2.5 patterns (rainy season, transition season and dry season). PM2.5 pollutant trajectory patterns were obtained using a single-Particle Lagrangian Integrated (HYSPLIT) forward trajectory derived from NOAA (National Oceanic and Atmospheric Administration). Then the correlation between PM2.5 with meteorological parameters during 2016-2017 was analyzed. The results showed the maximum concentration of PM2.5 in 2016 occurred in the dry season (June-August) of 57.43 µg/m3 and decreased for 2017 by 50.84 µg/m3. Meanwhile, minimum PM2.5 concentration occurs during the rainy season (December-February) which is equal to 20 µg/m3 in 2016, in 2017 PM2.5 decreases to 15.5 µg/m3. The results of running model (HYSPLIT) forward trajectory of PM2.5 pollutants show when dry season pollutant leads to the western part of Jakarta city while the PM2.5 pollutant in rainy season moved from Jakarta city leads to the eastern region.